2020
DOI: 10.3390/ijms21218042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deoxycholic Acid on Oesophageal Adenocarcinoma Invasion: Effect on Matrix Metalloproteinases

Abstract: Bile acids (BAs) have been implicated in the development of oesophagitis, Barrett’s oesophagus and oesophageal adenocarcinoma (OAC). However, whether BAs promote cancer invasiveness has not been elucidated. We evaluated the role of BAs, in particular deoxycholic acid (DCA), in OAC invasion. Migration and invasiveness in untreated and BA-treated oesophageal SKGT-4 cancer cells were evaluated. Activity and expression of different matrix metalloproteinases (MMPs) were determined by zymography, ELISA, PCR and West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Halvorsen et al also obtained similar results, that LCA promoted the secretion of matrix metalloproteinase 2 (MMP-2) and increased cellular invasion in human colon cancer cells (80). For DCA, several studies have confirmed its ability to promote invasion/migration in colon cancer and esophageal adenocarcinoma, but only at a low concentration (20 mM) (82,83). Pai et al concluded that at doses of 5 and 50 mM, DCA can enhance the invasiveness of colon cancer cells by activating b-catenin-cyclin D1 and -uPAR signaling pathways (55).…”
Section: Bile Acids In Cancer Cell Invasion and Metastasismentioning
confidence: 77%
See 3 more Smart Citations
“…Halvorsen et al also obtained similar results, that LCA promoted the secretion of matrix metalloproteinase 2 (MMP-2) and increased cellular invasion in human colon cancer cells (80). For DCA, several studies have confirmed its ability to promote invasion/migration in colon cancer and esophageal adenocarcinoma, but only at a low concentration (20 mM) (82,83). Pai et al concluded that at doses of 5 and 50 mM, DCA can enhance the invasiveness of colon cancer cells by activating b-catenin-cyclin D1 and -uPAR signaling pathways (55).…”
Section: Bile Acids In Cancer Cell Invasion and Metastasismentioning
confidence: 77%
“…also obtained similar results, that LCA promoted the secretion of matrix metalloproteinase 2 (MMP-2) and increased cellular invasion in human colon cancer cells ( 80 ). For DCA, several studies have confirmed its ability to promote invasion/migration in colon cancer and esophageal adenocarcinoma, but only at a low concentration (20 μM) ( 82 , 83 ). Pai et al.…”
Section: Bile Acids In Cancer Cell Invasion and Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…MMP-2 and MMP-9 are calcium-dependent zinc-containing endopeptidases that belong to the MMP family. MMPs are thought to play an important role in cell behavior, such as proliferation, migration (adhesion or dispersion), differentiation, angiogenesis, apoptosis, and host defense [ 33 , 34 , 35 , 36 , 37 ]. MMPs are involved in the disruption of the extracellular matrix in ischemic strokes, which leads to changes in the blood vessel wall and may loosen the matrix around cells, facilitating cellular swelling [ 38 ].…”
Section: Introductionmentioning
confidence: 99%